Supervisão e temas da religião: experiência de acolhimento - Machado, Aline Renata (2010)
Psychological literature points out that religion is a neglected subject, mainly by psychologists. These professionals face a lack of preparation to deal with religious questions within their practices. Most studies handle the subject matter highlighting its difficulties, so it is important to address it through its positive aspects. Thus, the purpose of this dissertation is to question and comprehend the ability of the supervisor, which is the professional who deals with the subject of Psychology and religion among the trainees in school clinics, in order the students feel comfortable. To reach this purpose, three interviews were conducted with a school clinic supervisor, selected by the students as someone who welcomes questions related to the religious dimension. A qualitative research was developed on a phenomenological basis, and aimed to investigate the supervisor s experiences through semi-structured interviews. The interviews´ analysis pointed out that it is possible to welcome religious questions that emerge during supervision as any other topic, and that this welcoming is provided by a significant learning approach, as a result of a transforming dialogic-based relationship provided by an active listening. This relationship allows the student to talk about this subject without the fear of being judged; the supervisor takes into consideration her students´ life experiences, focusing her own feelings and thoughts so it is possible for the students to open themselves to the others. Her attitude is influenced by her vision of mankind, her life experiences, her theoretical approach and how she conceives religion. Knowing the experience of the teacher, who is seen by the students as someone who can embrace the themes of religion may help others responsible for the training of psychologists, to provide conditions for students to reflect without fear and prejudice on religious matters and their role in human life